Correlation and path coefficient analysis in Giant Taro (Alocasia macrorrhiza L.) (Bangladesh Journal of Scientific and Industrial Research, 2015)
Genotypic and phenotypic character associations as well as direct and indirect effects were estimated for eleven characters such as plant height, petiole length, petiole breadth, leaf area index, inflorescence length, spathe length, spathe breadth, corm length, corm breadth, corm weight and yield per plant, in giant taro (Alocasia macrorrhiza L). The results revealed that plant height, LAI, corm length, corm breadth, had positive correlation with yield per plant both at genotypic and phenotypic level. Relatively higher positive and direct effect was found through petiole length, LAI and corm length and yield per plant in genotypic level. The residual effect 0.4762 represent in genotypic level about 53 % of the variability observed for yield per plant was represented by these traits. In the phenotypic level highest and positive direct effect was observed with petiole length and yield per plant. Positive direct effect was also found on yield per plant by plant height, petiole length, inflorescence length, inflorescence number, spathe length and spathe breadth, corm length, corm breadth. The residual effect 0.4235 means that characters included in the present study explained about 58 % variability in yield per plant at phenotypic level.Bangladesh J. Sci. Ind. Res. 50(2), 117-122, 2015